The development of the concept of macro-micro nutrients and its implications for early childhood: a literature review - Lubis, Eka Jelita; Karima, Karima; Nabila, Mauliza; Khairani, Rida; Khadijah, Khadijah (EDUCTUM: Journal Research, 2026)
The development of nutritional science shows a paradigm shift from quantitative nutritional fulfillment to a more comprehensive approach oriented towards the quality of early childhood growth and development. This study aims to examine the development of the concept of macro and micronutrients and analyze their implications for the growth and development of early childhood. This study used a qualitative approach with a systematic literature review method. Data sources were obtained from academic books and articles from accredited national and reputable international journals published between 2020 and 2024. The data were analyzed using content analysis and thematic analysis to identify key concepts, patterns of findings, and the relationship between nutritional fulfillment and child development. The results of the study indicate that the concept of macronutrients has evolved from merely a source of energy to become an important component in brain development, the immune system, and metabolic regulation, while micronutrients play a strategic role in immune function, neurodevelopment, and the prevention of developmental disorders. A balanced provision of macro and micronutrients has been shown to have positive implications for physical growth, cognitive development, language, socio-emotional development, and the long-term health of early childhood. This study emphasizes the importance of an integrative and holistic approach to nutrition as a basis for planning sustainable early childhood nutrition interventions.